The Effect Of Time Variation and Sodium Chloride (NaCl) Concentration In The Sedimentation Method On Soil-Transmitted Helmints (STH) Examination - Acivrida Mega Charisma; Arina Wahyuningrum (Jurnal Teknokes, 2025)
Soil-transmitted helminths (STH) remain a significant public health concern, particularly in regions with inadequate sanitation. While the sedimentation method is routinely employed for STH diagnosis, the effects of procedural variables such as incubation time and sodium chloride (NaCl) concentration on recovery efficiency remain inadequately explored. This study aimed to evaluate the influence of variations in sedimentation time and NaCl concentration on the detection and morphological integrity of STH eggs in stool samples. This contributes to more reliable diagnostic results in laboratory settings, supports epidemiological surveillance, and enhances the accuracy of STH monitoring in endemic areas. A controlled experimental design was implemented, utilizing 48 treatment combinations that varied in NaCl concentration (2%, 4%, 6%, and 8%) and sedimentation duration (5, 10, 15, and 20 minutes). Stool samples naturally infected with Ascaris lumbricoides, Trichuris trichiura, and hookworm were processed and examined microscopically for egg count, morphology, and sedimentation quality. Data normality was assessed using the Shapiro–Wilk test, and differences among treatment groups were analyzed with the Kruskal–Wallis test followed by post-hoc pairwise comparisons. Results demonstrated that both NaCl concentration and sedimentation time significantly influenced egg recovery (p < 0.05), with 2% NaCl and 30 minutes yielding the highest recovery rate and optimal morphological preservation. Morphological assessment revealed that prolonged sedimentation (>40 minutes) resulted in noticeable egg deformation, potentially compromising identification accuracy. These findings highlight the critical importance of optimizing procedural parameters in routine STH diagnostics. Adjusting NaCl concentration and sedimentation time can enhance both quantitative recovery and qualitative morphological assessment, thereby improving diagnostic reliability in clinical and epidemiological settings. In conclusion, the study provides evidence-based recommendations for sedimentation protocols, bridging a methodological gap and offering practical guidance for parasitology laboratories aiming to enhance the accuracy of STH examinations.